2000
DOI: 10.1046/j.1464-410x.2000.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in the erectile tissues of diabetic and healthy rats

Abstract: Objective To compare the frequency of apoptosis in the erectile tissue of chronic diabetic and healthy rats. Materials and methods Fourteen chronic diabetic and 10 healthy Sprague±Dawley rats were killed, their penises harvested and stored at ±70uC until staining and¯ow cytometric analysis for apoptosis. A cell suspension was obtained from the penile tissue by scraping the inside of the cavernosum with a scalpel and ®ltering through a mesh. Samples of the cell suspension (0.5r10 6 cells) were stained with Anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 21 publications
3
33
0
3
Order By: Relevance
“…Finally, in accordance with previously reported studies, we observed also that although apoptosis was increased in diabetic cavernosal penises, both sildenafil and sildenafil þ ALT-711 treatments prevent the apoptotic effect of diabetes in cavernosal tissue. 24,25 In our study, 5-HMF and MDA were indicators for penile tissue AGEs and oxidative stress, respectively. Both parameters were increased in diabetic penile tissue, whereas they were both decreased after sildenafil þ ALT-711 treatment.…”
Section: Discussionmentioning
confidence: 49%
“…Finally, in accordance with previously reported studies, we observed also that although apoptosis was increased in diabetic cavernosal penises, both sildenafil and sildenafil þ ALT-711 treatments prevent the apoptotic effect of diabetes in cavernosal tissue. 24,25 In our study, 5-HMF and MDA were indicators for penile tissue AGEs and oxidative stress, respectively. Both parameters were increased in diabetic penile tissue, whereas they were both decreased after sildenafil þ ALT-711 treatment.…”
Section: Discussionmentioning
confidence: 49%
“…Earlier reports have demonstrated myocardial apoptosis in diabetic patients (Frustaci et al, 2000) as well in diabetic animal models (Kajstura et al, 2001;Cai et al, 2002). Furthermore, apoptosis associated with raised level of oxidative stress in multiple organ systems in diabetes mellitus has been well documented (Alici et al, 2000;Cai et al, 2000). Thus, striking suppression of ROS levels could have attributed to the decrease in the apoptotic counts suggests the protective effect of paeonol on cardiac tissue.…”
Section: Discussionmentioning
confidence: 93%
“…Different researchers showed increased endothelial apoptotic cell density in diabetic erectile tissue. [21][22][23] Diabetes has known pathological effects on peripheral tissue innervations and vascularization, both of which are important for the erectile function. 24 In addition, it causes oxidative stress, which has a key role in the pathogenesis of diabetes-associated ED acting on blood vessel endothelia, peripheral nerves and smooth muscles and inducing cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%